Perubahan tarif pajak penghasilan badan menurut undang-undang pajak penghasilan no. 36 tahun 2008 dan praktik earnings management - EDDY JONI (Jurnal Bisnis dan Akuntansi, 2015)
This study aimed to examine the practice of earnings management before and after the change in corporate income tax rates with Tax Law No. 36 of 2008 on income tax. Earnings management in this study using two approaches, which are discretionary accruals and deferred Tax. Further research will analyze the factors that affect the practice of earnings management proxy variables with the tax incentives of tax planning and tax incentives to non proxy earnings pressure, debt levels, audit quality, growth, and profitability. This study uses a total of 51 companies registered profits in the Indonesia Stock Exchange during the period of observation years from 2007 to 2010. Total observations in this study are 204. The results prove that (1) The Company does not make earnings management in response to changes in corporate income tax rates in Indonesia, (2) earnings pressure influences discretionary accruals, (3) earnings pressure, debt levels and profitability influence deferred tax.